FORMATION OF READINESS SKILLS FOR LEARNING IN ORGANIZING THE EDUCATIONAL PROCESS (TAMADDUN NURI JURNALI, 2024)
The article analyzes the factors that should be taken into account when starting the educational process. In this regard, opinions were expressed on some aspects that can be tolerated. Today, it is emphasized the need to solve this issue while studying the rich scientific heritage of our ancestors.